How to write a good teaching case : RSM CDC case writing training material part 2 - Yue, Tao, active 2024 (London : Rotterdam School of Management, Erasmus University, 2024)
A teaching case is a dynamic tool that encapsulates real-world management situations, serving as a challenge or opportunity for organizations. Its style is vibrant, realistic, and compelling, pushing students to take on decision-maker roles, fostering analytical thinking, and nurturing creativity. Unlike research papers, teaching cases are more akin to thrilling narratives, revolving around a pivotal "decision focus." Engaging storytelling is essential, featuring balanced perspectives and often incorporating elements of controversy, conflict, or dilemma. A good teaching case is concise, rich enough for analysis, and thought-provoking, often revealing hidden layers upon closer examination. This abstract provides insight into the key considerations when creating a teaching case, ranging from its alignment with teaching objectives to the interview process, case structure, and writing style. Teaching cases are powerful tools for educators and researchers, combining the intrigue of storytelling with the practicality of management insights.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Decision making -- Study and teaching -- Case studies; Storytelling -- Case studies